CAMPUR KODE DALAM CHANNEL YOUTUBE “NIHONGO MANTAPPU” - Achmad Zhaky Alfajri; Merri Silvia Basri; Yenny Aristia Nst (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: In the current era of globalization, the use of language is growing rapidly. The demand for mastering a foreign language is even greater. With the advancements in the current era of globalization, not only English, Japanese is also the language learned by speakers of the language as a foreign language or a second language. These linguistic events will appear in a multilingual society related to sociolinguistics. Someone who is communicating with the other person actually sends codes to the other person which can lead to the process of code switching and code mixing. Code mixing is mixing code from one language to another, expanding the language style or variety of languages.. The phenomena of code-switching and code-mixing are actually a phenomenon that often occurs in everyday life but is not widely realized by the speakers. The purpose of this study is to describe the types and causes of code switching contained in the Nihongo Mantappu Youtube channel. The method used in this study is the listening method with the free-involved-talk (SBLC) listening technique. In this study, 14 code mixing data were found with 18 code mixing utterances.Key Words : sociolinguistics, multilingual, code mixing